Cephalic Index in Indigenous Tharu Community - Sanzida Khatun (Journal of Nepal Medical Association, 2018)
Introduction: Cephalic index is an important parameter for differentiation of race and sex which varies significantly on the basis of hereditary, geographical, racial, sexual and other factors. It is a morphometric expression of different forms of head. The objective of this research was to evaluate the cephalic index of people of indigenous Tharu community of Biratnagar, Nepal and to determine different head types.